Oral mucositis with abiraterone acetate: A therapeutic dilemma - Shaunak Valame; G Sharat Chandra; Dipanjan Panda; Atul Sharma (Indian Journal of Medical and Paediatric Oncology)
Mucositis is a common complication of cancer treatment. Mucositis has varied etiology. Here, we describe a case of 71-year-old male with metastatic castrate-resistant carcinoma prostate who developed mucositis with the use of targeted therapy, and this particular scenario led to the therapeutic dilemma.